Implementation of Islamic education curriculum at Ma'had At tarbiyah Sasnupatham school Pattani province (Southern Thailand) - Septoyadi, Zikry; Candrawati, Vita Lastriana; Duerame, Adel; Junanah, Junanah (IAIN Salatiga, 2021)
The author's reason for choosing the title is to find out the implementation of pesantren based Islamic education curriculum in Sasnupatham School, which has become a phenomenon in the world of education so that at the time of its founding, it can still attract public interest to include their children in school at Ma'had At tarbiyah. The data source of this consists of the first, the source of the literature is the books that are used as a theoretical basis including the curriculum of Islamic Education and Islamic Education curriculum in Sasnupatham. The approach in this study used a qualitative descriptive, in conducting the research. In obtaining data, the authors used observation, interview and documentation techniques. After our observation with the teacher, our students will talk about the history of this school, and we can say that the Sasnupatham school used to be a boarding school and in the cottage also taught the yellow book, after that how many years later then the school building for students could learn more broadly, we have talked with our teacher that we will relax in this school, because we will love this school, and this school is what makes us good and successful people.